Nilai-Nilai Pendidikan Islam Dalam Tradisi Kenduri Di Dusun Sumber Desa Lumajang Kabupaten Wonosobo - Fuadi, Salis Irvan; Fuad, Fuad; Zuhdi, Ahmad (Matan : Journal of Islam and Muslim Society, 2022)
The values ​​of Islamic education are something that becomes a belief and encourages people to always do good in life, both in family life, society, and relationships with God. While the Kenduri tradition is a tradition that is still carried out and maintained by the people of the Sumber hamlet. The objectives of this study are: 1) to find out about the procession of the Kenduri Tradition implementation; 2) to know the values ​​of Islamic education in the Kenduri tradition; 3) to find out the meaning of the Kenduri tradition for the people of Sumber Hamlet. In this study, using a qualitative approach with the type of field research field research that is descriptive because the author will describe and describe in full and in depth social reality based on existing facts, so that the characteristics, characters, characteristics and models of the phenomenon are described. The data were obtained from the informants using interview, observation and documentation techniques, then analyzed the data obtained, then data reduction, data presentation, and conclusions were drawn from the research. From the research carried out, the research results obtained consisted of: the procession of implementing the Kenduri tradition, which begins with a pilgrimage to the grave, then welcomes from the sohibul hajat, tahlilan together, recites a prayer together, and closes by eating a meal together, after that gets a blessing. in the form of food to take home. The values ​​of Islamic education contained in the Kenduri Tradition include: the value of faith education, the value of moral education, the value of worship education, and the value of social education. The Kenduri tradition has a great meaning for the people of Sumber hamlet, as an embodiment of gratitude to God for the blessings and gifts that have been given, and is a form of servitude to God and creates a closeness of togetherness between the people, and has benefits, especially strengthening ties of friendship.